The role of cosmic ray pressure in accelerating galactic outflows - Simpson, Christine M.; Pakmor, Rüdiger; Pfrommer, Christoph; Springel, Volker; Glover, Simon (Arxiv, 2016)
We study the formation of galactic outflows from supernova explosions (SNe) with the moving-mesh code AREPO in a stratified column of gas with a surface density similar to the Milky Way disk at the solar circle. We compare different simulation models for SNe placement and energy feedback, including cosmic rays (CR), and find that models that place SNe in dense gas and account for CR diffusion are able to drive outflows with similar mass loading as obtained from a random placement of SNe with no CRs. Despite this similarity, CR-driven outflows differ in several other key properties including their overall clumpiness and velocity. Moreover, the forces driving these outflows originate in different sources of pressure, with the CR diffusion model relying on non-thermal pressure gradients to create an outflow driven by internal pressure and the random-placement model depending on kinetic pressure gradients to propel a ballistic outflow. CRs therefore appear to be non-negligible physics in the formation of outflows from the interstellar medium.